Christus phiLosophicus - The Relevant Message of Early Christian Art for Our Times. Reflections on Cardinal Joseph Ratzinger's lecture Faith, PhiLosophy and TheoLogy. - Grzeszczak, Jan (Filozofia Chrześcijańska, 2009)
The article consists of a discussion about selected issues which were taken up in Cardinal Ratzinger’s lecture, Faith, Philosophy and Theology. The lecture was delivered by the Cardinal in 1984 on the occasion of receiving an honorary doctorate from the College of St. Thomas in St. Paul, Minnesota. In his lecture, Joseph Ratzinger refers to the first images of Christ that can be seen on the sarcophagi which date from the early centuries of the Church (the Good Shepherd, the Philosopher, etc.). According to Ratzinger, these depictions constitute an attempt to provide a Christian reply to questions about the sense of death. Today, this issue can bring theology and philosophy together and assist in the search for a new rationale.